Single-Incision Laparoscopic Surgery for Undiagnosed Small Bowel Obstruction in a Patient without a History of Abdominal Surgery - Noriaki Koizumi; Hiroki Kobayashi; Tsuyoshi Takagi; Kanehisa Fukumoto (Case Reports in Surgery)
We herein report a 66-year-old female patient who developed an undiagnosed small bowel obstruction without a history of prior abdominal surgery and was successfully treated by single-incision laparoscopic surgery. A small bowel obstruction with unknown cause typically requires some sort of surgical treatment in parallel with a definitive diagnosis. Although open abdominal surgery has been generally performed for the treatment of small bowel obstructions, laparoscopic surgery for small bowel obstructions has been increasing in popularity due to its less invasiveness, including fewer postoperative complications and a shorter hospital stay. As a much less invasive therapeutic strategy, we have performed single-incision laparoscopic surgery for the treatment of an undiagnosed small bowel obstruction. We were able to make a definitive diagnosis after sufficient intra-abdominal inspection and to perform enterotomy through a small umbilical incision. Single-incision laparoscopic surgery appears to be comparable to conventional laparoscopic surgery and provides improved cosmesis, although it is an optional strategy only applicable to selected patients.